Identification of four immune subtypes in locally advanced rectal cancer treated with neoadjuvant chemotherapy for predicting the efficacy of subsequent immune checkpoint blockade - He, Le; Jin, Min; Jian, Dan; Yang, Bo; Dai, Nan; Feng, Yan; Xiao, He; Wang, Dong (Frontiers in Immunology, 2022)
Introduction Neoadjuvant chemoradiotherapy (nCRT) is the foundation treatment for locally advanced rectal cancer (LARC). The nCRT can improve the efficacy of immunotherapy because of its in situ vaccine effect. Objective The aim is to identify stable and reliable transcriptome signatures to predict the efficacy of immune checkpoint blockade (ICB) in patients with LARC. Methods Immunophenotyping was established using xCell immune cell infiltration abundance and consistent clustering in GSE39582 and verified in several data sets. The effects of immunophenotyping, follicular regulatory T cells, tumor-associated fibroblasts (CAFs), and tertiary lymphoid structure (TLS) signatures on the efficacy of ICB were analyzed using IMvigor210, GSE91061, and an independent Daping Hospital (DPH) cohort. Results There are four stable and repeatable immune subtypes in rectal cancer, among which C1 is a low immune infiltration type, C2 is a high interstitial infiltration type, C3 is a high immune infiltration type, and C4 is an ion channel type. C2 is mainly characterized by high infiltration of CAF. C3 is characterized by high infiltration of cytotoxic T lymphocytes, high expression of PD-L1 and TLS. In rectal cancer patients receiving nCRT, immunophenotyping was not significantly associated with pathological remission rate, but immunophenotyping was an independent prognostic factor of RFS. In IMvigor210 patients treated with atezolizumab, the pathological remission rates of C1, C2, C3, and C4 were 23.86%, 10.94%, 33.33%, and 23.08% respectively (χ2 = 8.981, P = 0.029), which were 11.76%, 50.00%, 42.86%, and 0.0% respectively in the GSE91061 patient treatment with nivolumab (Fisher’s exact probability, P = 0.018). Both follicular regulatory T cells and CAF showed a further impact on the ICB therapeutic efficacy of C2 and C3 subtypes. Additionally, both the GSE91404 and DPH cohorts showed that nCRT treatment induced a significant increase in the expression of TNFRSF9 and the abundance of macrophages in the C3 subtype. Conclusion Our data suggest that there are four immune types of rectal cancer, which are related to the prognosis of patients. Among them, C3 and some C2 subtypes represent the patients who may benefit from ICB after nCRT treatment.